2022
DOI: 10.1155/2022/7415769
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Environmental Regulation, Financial Resource Allocation, and Regional Green Technology Innovation Efficiency

Abstract: This paper empirically studies the environmental regulation, financial resource allocation, and regional green technology innovation efficiency by using provincial panel data from 2005 to 2019. The results show that the cost-input environmental regulation is negatively correlated with the efficiency of regional green technology innovation, while the government-subsidized environmental regulation is positively correlated with the efficiency of regional green technology innovation. The mechanism test shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…To ensure the authenticity and reliability of the conclusion, this paper draws on the practice of Bao and Chai [ 38 ]. Moreover, it conducts a robustness test on the general linear and panel threshold regression models.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure the authenticity and reliability of the conclusion, this paper draws on the practice of Bao and Chai [ 38 ]. Moreover, it conducts a robustness test on the general linear and panel threshold regression models.…”
Section: Resultsmentioning
confidence: 99%
“…Li found that environmental regulation and government R&D funding have a positive impact on enterprises' green technology innovation, and the coupling of the two has a stronger effect on green technology innovation [11]. Bao and Chai [12] empirically found that environmental regulation is positively correlated with regional green innovation efficiency, and the government improves the efficiency of green innovation by improving the allocation of financial resources [10][11][12]. Therefore, the study of Porter's hypothesis further proves that there is an "innovation effect" on the impact of environmental regulation on green technology.…”
Section: The Impact Of Environmental Regulation On Egiementioning
confidence: 99%
“…There are more existing indicators around the measurement of governmental environmental regulation, and most of the existing studies have used indicators such as investment in environmental management of pollution and collection of sewage charges to measure governmental environmental regulation. This paper draws on Bao and Chai to use the share of government environmental protection expenditure in fiscal expenditure to measure environmental regulation [12].…”
Section: The Explanatory Variable (Gser)mentioning
confidence: 99%
“…However, in order to meet the requirements of strict environmental regulations established by the government, green technology innovation will generate compliance costs at the initial stage of implementation, that is, increase the investment in pollution control (Gray and Shadbegian, 2019). This will cause the investment of actual production to be crowded out and soon increase the total cost, which will reduce the productivity and market competitiveness of enterprises (Bao and Chai, 2022). Second, R&D risk effect refers to the uncertainty of emerging green products, processes and technologies and the uncertainty of the external environment when enterprises carry out green technology innovation.…”
Section: Literature Reviewmentioning
confidence: 99%